Understanding the Socioemotional Worlds of English Learners: A Retrospective Study. Issue 2 (3rd April 2018) - Vera, Elizabeth; Hook, Kimberly; Daskalova, Plamena; Hill, Lincoln; Galvin, Sarah; Fritsche, Sarah; Catellier, Jessica; Haywood, Shaakira; Raziuddin, Abdul; Anderson, Bernasha; Roche, Meghan; Floro, Marissa; et al.
ABSTRACT: This mixed-methods study examined the socioemotional experiences of 57 alumni of language support programs (i.e., English as a second language, bilingual education) to identify effects of being English learners (ELs). Findings revealed the need for multicultural sensitivity to ELs, bullying episodes, social exclusion, and not disclosing negative experiences. Participants valued opportunities to meet diverse peers, appreciated teacher support, and viewed negative experiences as a source of motivation to achieve. Participants with greater numbers of negative experiences were less connected to ethnic communities, were more marginalized by their ethnic peers, and had lower school belonging. School- based support was correlated with school belonging and overall perceptions of support. Years in ESL classrooms was correlated with negative affect. Support from school and family along with ethnic identity and sense of connection to ethnic community were significant predictors of positive affect. Findings have implications for consultation and professional development of personnel working with ELs.